Investigating the impact of embedded generation on relay settings of utilities electrical feeders. - Salman, S.K (IEEE Transactions on power delivery)
Since the late 1970s, intensive efforts have been made to utilize renewable energy sources to generate electric power. On the other hand, economical pressure experienced in recent years has led to the development of high efficiency combined heat and power schemes to use the normally wasted heat to generate electric power. Generators used under both schemes can be either synchronous or asynchronous types and when they are integrated into utilities' distribution networks (DNs) they are commonly known as ?embedded generators? (EGs). Previous experience has shown that the integration of EGs into DNs could create safety and technical problems. They may contribute to fault currents, cause voltage flicker, interfere with the process of voltage control, etc. This paper reports an investigation to determine the impact of the integration of EGs on the settings of protective devices of electrical feeders emanated from the substation to which EGs are connected. This study also covers the dynamic behavior of EG caused by disturbances on the host network. Results obtained from several case studies presented and discussed